AB0114 Semaphorin3a and semaphorin4d in rheumatoid arthritis. (23rd January 2014) - Yoshida, Y.; Kang, S.; Morishima, A.; Akihiko, N.; Hishitani, Y.; Maeda, Y.; Nishide, M.; Hamano, M.; Morimoto, K.; Hirano, T.; Shima, Y.; Narazaki, M.; et al.
Abstract : Background: Semaphorins are involved in a wide range of biological processes, including neuronal axon guidance, angiogenesis, immune modulation and osteogenesis (1, 2 ). Semaphorin 3A (Sema3A) suppress osteoclast function and increase osteoblast function (3 ). Semaphorin 4D (Sema4D), which is expressed by osteoclast, suppress osteoblast function (4 ). Sema4D and 3A might be key mediators of osteoimmunology in rheumatoid arthritis (RA), which have immune activation associated bone destruction. Objectives: To determine the pathogenic role of Sema3A and Sema4D in RA, we evaluated the serum level of Sema3A and Sema4D in RA patients. Methods: Concentrations of Sema3A and Sema4D in 102 RA patients and 26 normal controls were measured by ELISA (Mybiosource). Results: The serum concentrations of Sema4D in RA patients and normal controls were 11.16±8.49 and 5.87±3.10ng/ml respectively (p<0.00001). The serum concentrations of Sema 3A in RA patients and normal controls were 8.97±3.71 and 6.65±3.75 ng/ml respectively (p<0.01). Serum concentrations of Sema4D in RA patients were associated with disease activity (DAS28 r=0.38, p<0.01, CRP r=0.34, p<0.01), rheumatoid factor (RF) (r=0.33, p<0.01) and marker of bone metabolism (urine deoxypyridinoline r=0.32 p<0.05). However serum Sema3A didn't associated with disease activity and marker of bone metabolism. Image/graph: Conclusions: Serum concentration of Sema3A and Sema4D were elevated in RA patients. In particular Sema4D showed association with disease activity, RF, and marker of bone metabolism. Semaphorins may play an important role in RA by immune activation, angiogenesis, increasing primary afferent sensory fibers with sympathetic nerve fiber repulsion in synovium, and bone destruction in joints. References: Kumanogoh A et al. Immunity. 2000;13:621-31. Takamatsu H et al. Nat Immunol. 2010;11:594-600. Negishi-Koga T et al. Nat Med. 2011;17:1473-80. Hayashi M et al. Nature. 2012;485:69-74. Disclosure of Interest: None Declared